Development of a New Composite Index for Measuring Sustainability Performance of Manufacturing Companies Operating in BIST Sustainability Index - Soner Alaca; Mustafa Tepeci (Journal of Economy Culture and Society)
The number of studies on sustainability assessment tools and models has increased in the last two decades. Composite Indexes (CIs) have become popular as a useful tool for assessing business level sustainability to compare the companies operating in the same sector. Limited studies have covered all three dimensions (economic, environmental, and social) of the sustainability assessment in an integrated manner in Turkey. This paper aims to measure and evaluate the Corporate Sustainability (CS) performances of ten manufacturing companies operating in the Istanbul Stock Exchange Market. For this purpose, a new integrated sustainability composite index was developed by using previous composite indexes in the literature. The developed assessment model provides a practical tool for the organizations in the manufacturing sector in Turkey by measuring and evaluating their sustainability performances in a holistic way. By using the analytical hierarchy process (AHP), the levels of the sustainability performances of ten manufacturing organizations were assessed in a short time. The index allows managers to make comparisons among companies within the same sector. The results further indicated that the economic dimension score of the analyzed organizations had a weighty and salient effect on the total corporate sustainability performance score. This finding contributes to the literature that economic performance is predominantly effective in the sustainability performance of businesses.